Pengaruh Penerapan Model Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Berpikir Kritis Siswa Ditinjau dari Self esteem - Nurwati Djam’an; Fajar Arwadi; Nurul Amini (Issues in Mathematics Education (IMED), 2023)
This study aims to determine whether there is an effect of the application of the guided inquiry learning model on critical thinking skills in terms of self-esteem. The sampling technique in this study used a random sampling technique and the number of samples was 26 students. Data collection techniques are using test and non-test instruments. The instruments used are tests of students' critical thinking skills, self-esteem questionnaires, and learning implementation observation sheets. The data analysis technique used is descriptive statistical analysis and inferential statistics with simple linear regression analysis. The results showed that: (1) The application of the guided inquiry learning model had no effect on the critical thinking skills of students in the SER category (low self-esteem), (2) The application of the guided inquiry learning model had an effect of 27.3% on the critical thinking skills of students in the SES category ( moderate self-esteem), and (2) the application of the guided inquiry learning model has an effect of 82.8% on the critical thinking ability of students in the SET category (high self-esteem).